Peningkatan Hasil Belajar Siswa Menggunakan Model PBL Pada Pembelajaran Tematik Terpadu Kelas V SD - Hilda Ismah; Yunisrul Yunisrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to describe the planning, implementation and improvement learning outcomes of students using a problem based learning model in integrated thematic learning in grade V Elementary School. In this study applying the type of PTK research uses qualitative and quantitative approaches. Where this research was conducted on class V B SD Kartika 1-11 Padang totaling 20 people consisting of 9 male students and 11 female students. The results of the study in the first cycle of learning outcomes reached a percentage of completeness of 25% (Less category) with an average value of 3.12 (good category) increased in the second cycle percentage of completeness 90% (very good category) with an average achievement of 3.75 (very good category).